Pengaruh Indeks Saham Asing Dan Variabel Makroekonomi Terhadap Indeks Harga Saham LQ45 - Anisa Fitri Ani; Thomas Andrian (Universitas Negeri Padang, 2022)
Investment is one kind of country’s income. The capital market, including stocks, is a form of the convenience of modern investment. Investors, policy makers, capital market observers, and financial analysts need information in monitoring the movement of traded stock prices. Stock index is the main information in the stock market. One of the stock indexes which have potential and noticed by the people is the LQ45 stock price index. In this study, researchers tried to determine the effect of foreign stock index the Dow Jones Industrial Average (DJIA) and Straits Times Index (STI) and macroeconomic variables such as the USD/IDR exchange rate, interest rates (BI 7-days (Reverse ) Repo Rate), and inflation on the LQ45 stock price index. This study uses the Error Correction Model (ECM) method with 60 observational data from the research period January 2017 to December 2021. The results show that DJIA and STI have a positive and significant effect in the long and short term, the exchange rate has a negative and significant effect in the long and short term, interest rate has a negative and insignificant effect in the short term while in the long term it has a significant positive effect, while inflation has an insignificant negative effect in the long and short term on the LQ45 stock price index.